2004
DOI: 10.1038/sj.sc.3101647
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of spasticity with intrathecal Baclofen administration: long-term follow-up, review of 40 patients

Abstract: Study design: Case series of a consecutive sample. Retrospective audit. Objective: To analyze the long-term safety and efficacy of intrathecal baclofen (ITB), and technical incidents. Setting: Neurosurgical and Physical Medicine Departments of two university hospitals in western France. Methods: The medical records of 40 patients who underwent ITB pump placement for the treatment of severe chronic spasticity were reviewed. Patients were eligible independently of the origin of the spasticity (spinal cord origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
80
3
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 48 publications
5
80
3
5
Order By: Relevance
“…The infection rate per year was between 0.7 and 5.2%. 3,7,[10][11][12][13][14][15] With a total observation period of 552 pump years, our study unequivocally covers the longest observation period. The annual rate for complications requiring surgical measures was 10.5%.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The infection rate per year was between 0.7 and 5.2%. 3,7,[10][11][12][13][14][15] With a total observation period of 552 pump years, our study unequivocally covers the longest observation period. The annual rate for complications requiring surgical measures was 10.5%.…”
Section: Discussionmentioning
confidence: 79%
“…2,3 Meanwhile, a series of studies has shown the effectiveness of continuous intrathecal therapy for both spinal or cerebral spasticity [3][4][5][6][7][8] and chronic pain. 9 The inadequate efficacy and intolerable side effects of oral and transdermal pharmacotherapy for the relief of symptoms in a considerable proportion of patients have led to the increased popularity of intrathecal therapies over the past two decades.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of nonlocalised spasticity by use of intrathecal baclofen has proven effective in relieving symptoms, 29 although it is clear that patients frequently suffer complications. 30 Intrathecal baclofen may also improve neurogenic bowel 31 and increase functional bladder capacity and compliance. 21,31 These effects may act synergistically and improve quality of life 28 and sexual function.…”
Section: Bowel Incontinencementioning
confidence: 99%
“…[1,2,5,6] Initially, we suspected it to be seroma, so just a compressive dressing was applied. We avoided aspiration fearing that it may introduce infection.…”
Section: Discussionmentioning
confidence: 99%